Highly luminescent and cytocompatible cationic Ag2S NIR-emitting quantum dots for optical imaging and gene transfection. Issue 26 (12th June 2015) - Duman, Fatma Demir; Hocaoglu, Ibrahim; Ozturk, Deniz Gulfem; Gozuacik, Devrim; Kiraz, Alper; Yagci Acar, Havva
Abstract : Cationic Ag2 S quantum dots that are strongly luminescent in the NIR-I region with a quantum yield as high as 150% are developed by a simple aqueous technique. In vitro optical imaging and gene delivery experiments have demonstrated their value as new theranostic materials. Abstract : The development of non-toxic theranostic nanoparticles capable of delivering a therapeutic cargo and providing a means for diagnosis is one of the most challenging tasks in nano-biotechnology. Gene therapy is a very important mode of therapy and polyethyleneimine (PEI) is one of the most successful vehicles for gene transfection, yet poses significant toxicity. Optical imaging utilizing quantum dots is one of the newer but fast growing diagnostic modalities, which requires non-toxic, highly luminescent materials, preferentially active in the near infrared region. Ag2 S NIRQDs fit to this profile perfectly. Here, we demonstrate the aqueous synthesis of cationic Ag2 S NIRQDs with a mixed coating of 2-mercaptopropionic acid (2MPA) and PEI (branched, 25 kDa), which are highly luminescent in the NIR-I window ( λ em = 810–840 nm) as new theranostic nanoparticles. Synergistic stabilization of the QD surface via the simultaneous use of a small molecule and a polymeric material provided the highest quantum yield, 150% (with respect to LDS 798 at pH 7.4), reported in the literature for Ag2 S. These cationic particles show a dramatic improvement in cytocompatibility even without PEGylation, a strong optical signal easily detected by confocal laser microscopy and effective conjugation and transfection of the green fluorescence protein plasmid (pGFP) to HeLa and MCF-7 cell lines (40% efficiency). Overall, these Ag2 S NIRQDs show great potential as new theranostics.